Multi-slab hybrid radar absorbing structure containing short carbon fiber layer with controllable permittivity. (1st October 2021) - Jin, Do-Hyeon; Jang, Min-Su; Choi, Jae-Hun; Jang, Woo-Hyeok; Choi, Won-Ho; Kim, Chun-Gon
Abstract: This study proposed a multi-slab hybrid radar absorbing structure (RAS), containing short carbon fiber layers with controllable permittivity. The multi-slab hybrid composite is a structure in which a short carbon fiber layer, which is uniformly dispersed in a random direction, is inserted between glass fabrics. Multi-slab hybrid composites containing short carbon fiber layers with specific areal densities were fabricated to measure the complex permittivity. Through the measured complex permittivity, a multi-slab hybrid RAS was designed by controlling the areal densities of the short carbon fiber layers. As a result of measuring the electromagnetic wave absorption performance, the multi-slab hybrid RAS absorbed electromagnetic waves in the target frequency bands and improved the design flexibility of RAS.